1992
DOI: 10.2307/3578484
|View full text |Cite
|
Sign up to set email alerts
|

Possible Äccelerated Striatal Aging" Induced by 56 Fe Heavy-Particle Irradiation: Implications for Manned Space Flights

Abstract: The present experiments were carried out to determine the effects of energy deposition from energetic iron (56Fe particles, an important component of cosmic rays) on motor behavioral performance and to determine if the observed deficits were caused by alterations in the neostriatum (an important motor control area). Neostriatal function was assessed with two correlated parameters, i.e., motor behavioral performance (wire suspension task), and oxotremorine-enhanced K(+)-evoked release of dopamine from perifused… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
59
0

Year Published

1995
1995
2011
2011

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 127 publications
(60 citation statements)
references
References 32 publications
1
59
0
Order By: Relevance
“…Because amphetamine is a dopamine agonist, the development of an amphetamineinduced CTA requires an intact dopamine system (Rabin et al 1998), and the disruption of dopaminergic function by heavy particle irradiation interferes with behaviors that are dependent upon the integrity of that system. Overall, the deficits observed following exposure to HZE particles are similar to those that are observed in old animals, which suggest that exposure to low doses of HZE particles produces "accelerated aging" (Joseph et al 1992(Joseph et al , 1993.…”
Section: Introductionsupporting
confidence: 55%
See 3 more Smart Citations
“…Because amphetamine is a dopamine agonist, the development of an amphetamineinduced CTA requires an intact dopamine system (Rabin et al 1998), and the disruption of dopaminergic function by heavy particle irradiation interferes with behaviors that are dependent upon the integrity of that system. Overall, the deficits observed following exposure to HZE particles are similar to those that are observed in old animals, which suggest that exposure to low doses of HZE particles produces "accelerated aging" (Joseph et al 1992(Joseph et al , 1993.…”
Section: Introductionsupporting
confidence: 55%
“…Specifically, the 3-day interval was selected because previous experiments on the effects of exposure to HZE particles (Joseph et al 1992) had shown a maximal reduction in dopamine release 3 days following exposure to 56 Fe particles. In addition, research on the disruption of amphetamine-induced CTA learning has utilized a single injection of amphetamine on the conditioning day and a 24-h interval between conditioning and test days.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…These deficits are similar to those that are characteristic of the aged organism, including deficits in signal transduction (Joseph et al 1992(Joseph et al , 1993Casadesus et al 2005;Denisova et al 2002), amphetamine-induced taste aversion learning (Rabin et al 1998), spatial learning and memory using the Morris water maze Carey et al 2007), and operant responding . Previous research has shown that rats exposed to 56 Fe particles at a young age (2 months) show a progressive deterioration in operant responding on an ascending fixed-ratio (FR) reinforcement schedule as a function of time following irradiation such that doses of particles that did not affect the responding of younger animals did affect their responding as they aged (Rabin et al , 2005a.…”
Section: Introductionmentioning
confidence: 78%